Professional values, ethical climate and job satisfaction of nurses and their selected sociodemographic and occupational characteristics - Ozdoba, Patrycja; Jurek, Krzysztof; Dobrowolska, Beata (Frontiers in Public Health, 2024)
AimTo explore the relationship of selected socio-demographic and occupational characteristics of nurses and their level of professional values, hospital ethical climate and job satisfaction.MethodsCross-sectional study was conducted among 388 Polish nurses from the spring of 2021 to winter of 2023, in the eastern part of Poland; and followed by Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. Four research tools were used to collect data together with questionnaire for socio-demographic and occupational characteristics.ResultsProfessional values such as activism correlate negatively with religious beliefs (Z = −1.789; p = 0.044), this means that nurses who are more involved in professional change activities are likely to be less associated with religious beliefs. A positive correlation was observed between the Ethical Hospital Climate Survey subscale—peer relations and nurses’ education level (H = 5.638; p = 0.048), indicating that a higher education level was associated with better relationships with colleagues at work. A negative relationship was identified between nurses’ external job satisfaction and their marital status (Z = −1.958; p = 0.040), that is, married nurses feel less satisfaction with the external aspects of their jobs than their single colleagues.DiscussionThese findings underscore that medical staff management should take into account both sociodemographic factors [e.g., age, education, place of residence, marital status, religious beliefs, as well as professional factors (working hours, qualification course, etc.)] that affect nurses’ professional values, job satisfaction and the ethical climate of the hospital. These underscore the need to adapt management strategies to the individual needs of employees, which can contribute to improving working conditions in healthcare facilities.Data collection toolThe data collection tool consists of four sections.DemographicsCollected background and demographic information.Nurses’ professional values scale (NPVS-3)Assessed professional values among nurses.Hospital ethical climate survey (HECS)Assessed hospital ethical climate among nurses.Minnesota satisfaction questionnaire-short form (MSQ-SF)Assessed job satisfaction levels among nurses.